PENDEKATAN LEAN SIX SIGMA DALAM PENENTUAN PRIORITAS PERBAIKAN LAYANAN BANK BERDASARKAN PERSEPSI, HARAPAN DAN KEPENTINGAN NASABAH - Budiwati, Hesti (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
This research have a purpose to determine of improvement priority of banking services base on perception, expectation and interest level of the customer using lean sig sigma approach.Ã‚Â The result of this research are expected to give the contribute for the bank manager. This research will determine to recovery priority of service quality of the bank consisted of (1) effectiveness and assurance, (2) access, (3) price, (4) tangible, (5) service portofolio and (6) reliability. This research using lean sig sigma approach, to doing the calculation unwighted gap and weighted gap above the response ofÃ‚Â respondent base on perception, exspectation and interest level of the customer above the response of the responden base on perception, exspectation and interest level of the customer above servive quality of the bank. The population of this research is all active customera at PT. BPR Arta Centra Asia Lumajang, and sample of this research is taken as 120 customer as respondent. The result of this research showing at 3 (three) main priority of the recovery quality service of the bank that is dimension to reliability for the item the dont have a mistake in providing service, the dimension of the effectiveness is no delay because the birocation and procedure and service quickly. The next future this research are exspected to give the contribution to development of the study management science, especially for marketing management service, so it can be a reference for the similiarity of research and advance research.